Profile of Body Mass Index and Physical Fitness of Santri of Al Yumna Qur'an Tahfizh Boarding School - Asep Angga Permadi; Solahudin Solahudin; Azhar Ramadhana Sonjaya; Z. Arifin (Indonesian Journal of Physical Education and Sport Science)
Purpose of study. This study aims to determine the description of body mass index and physical fitness of students of the Al Yumna Banyuresmi Garut Tahfizh Islamic Boarding School, Garut.